Sanksi Hukum Penghinaan Terhadap Orang yang Sudah Meninggal Melalui Media Sosial di Indonesia - Kadek Suryasantosa; Anak Agung Sagung Laksmi Dewi; I Made Minggu Widyantara (Jurnal Konstruksi Hukum, 2021)
Currently, advances in information technology, globalization and electronic media are increasingly spreading in various fields of public life. This progress with the existence of an internet network is very easy to operate through the media, namely electronic media. The existence of it makes it easy for humans to do various things such as exchanging various information that can be obtained quite easily, and low cost. Therefore, people can do negative things that are not supposed to be done for their personal interests. This study aims to explain the legal arrangements for insulting people who have died and to explain criminal sanctions for criminal acts of humiliation through social media for those who have died. This research was designed using normative legal research methods, with a conceptual problem approach and a case approach. The data sources used are primary, secondary and tertiary legal data sources. Data were collected by recording, quoting, reading, and summarizing the literature referring to changes in gender status in Indonesia. After the data is collected, it is then analyzed systematically and relates it to legal materials. The result of this study indicates that Articles 320 and 321 of the Criminal Code will be used as the legal basis for a type of insulting act and Article 27 paragraph 3 of the ITE Law will be used for the basic purpose of a media that has been used. Furthermore, cases of insulting a deceased person can be subject to imprisonment for six (6) months as is the content of Article 446 paragraph I of the Draft Criminal Code but the legal process cannot proceed if there is no reporting from the family concerned.